Margin to Margin: Arts-Based Research for Digital Outreach to Marginalised Communities - Sarantou, Melanie Augusta; Akimenko, Daria; Escudeiro, Nuno (The Journal of Community Informatics, 2018)
This article discusses the artistic activity titled ‘Conversations with the edge’ that was executed by communities in Australia, Russia and Finland, and curated for an exhibition at the Helinä Rautavaara Museum in Espoo, Finland in 2017. This activity was created in the context of Margin to Margin: Women living on the edges of the world, a larger arts-based research project that took place between four geographical margins: outback South Australia, Finnish Lapland, Russian Kola Peninsula and Namibia. Margin to Margin was a collaboration between artist communities with the aim to explore the relationship between art-making and empowerment of makers living and working ‘on the edges’. The aim of the project was to understand the realities marginalised communities face whilst giving voice to these communities by exhibiting their art in various formats, stimulating digital participation and utilising technology for digital inclusion. The purpose of the article is to develop a model that will guide virtual arts-based project mediation for digital outreach in both urban and regionally situated marginalised communities.